A Critical Review of Methods and Results in the Search for Genetic Contributors to Alcohol Sensitivity. (5th April 2018) - Schuckit, Marc A.
Abstract : Attributes of alcohol sensitivity are present before alcohol use disorders (AUDs) develop, they predict those adverse alcohol outcomes, are familial in nature, and many are heritable. Whether measured by alcohol challenges or retrospective reports of numbers of drinks required for effects, alcohol sensitivity reflects multiple phenotypes, including low levels of alcohol response and alcohol‐related stimulation. Identification of genes that contribute to alcohol sensitivity could help identify individuals carrying risks for AUDs through their alcohol responses for whom early intervention might mitigate their vulnerability. Such genes could also improve understanding of biological underpinnings of AUDs, which could lead to new treatment approaches. However, the existing literature points to a wide range of genetic mechanisms that might contribute to alcohol responses, and few such genetic findings have been widely replicated. This critical review describes the potential impact of the diverse methods used to study sensitivity on the diversity of genetic findings that have been reported, places the genetic variants mentioned in the literature into broader categories rather than isolated results, and offers suggestions regarding how to advance the field by interpreting findings in light of the methods used to select research subjects and to measure alcohol sensitivity. To date, the most promising results have been for GABA, glutamate, opioid, dopamine, serotonin, and cholinergic system genes. The more gene variants that can be identified as contributors to sensitivity the better future gene screening platforms or polygenic scores are likely to be. Abstract : This review lists gene variants potentially related to alcohol sensitivity as measured by low levels of response to alcohol or alcohol‐related stimulation. The goal is to stimulate additional genetic research regarding alcohol sensitivity while describing potential differences across protocols used to measure the phenotype. I highlight the possibility that some aspects of alcohol sensitivity might relate to somewhat different gene sets and polygenic scores. The figure describes the steps likely to be used in testing phenotypes.